Effect of functional iron oxide nanocrystals on the arsenic level in drinking water - Paragas, Danila S.; De Guzman, Aileen G.; Paragas, Danika Jade S.; Imbag, Mark Dale S.; Dela Cruz, Laurenz O. (2011)
Arsenic is a semi-metal element in the periodic table and a naturally occurring element in the earth's crust. It enters drinking water supplies from natural deposits in the earth or from the agricultural and industrial practices. It has created serious contamination of the environment, causing many mass poisonings throughout the world. This study was designed to prepare functional iron oxide nanocrystals (a nanomagnet) and be used in the treatment of water contaminated with arsenic. The synthesis of functional iron oxide nanocrystals was divided into three parts: soap making process, extraction of oleic acid from soap with commercial vinegar, and preparation of magnetite or functional iron oxide nanocrystals from rust and fatty acids. The functional iron oxide nanocrystals (0.5 g per liter of water) was placed in water contaminated with arsenic and stirred for 5 minutes. The formation of bubbles on the surface of nanocrystals was observed. The water samples before and after the treatment was brought to the National Science Research Institute for analysis of arsenic using THGA Graphic Furnace Atomic Absorption Spectroscopic method. Results of the analysis showed that the functional iron oxide nanocrystals was able to remove 85.89% of arsenic. The removal of arsenic is through nanomagnetism. Further studies on the effect of different amounts of iron oxide nanocrystals and concentration of arsenic in water must be conducted.
Keywords: Drinking water; Water purification